Circulating tumour DNA is a promising biomarker for risk stratification of central chondrosarcoma with IDH1/2 and GNAS mutations. Issue 12 (30th September 2021) - Lyskjær, Iben; Davies, Christopher; Strobl, Anna‐Christina; Hindley, Joanna; James, Steven; Lalam, Radhesh K.; Cross, William; Hide, Geoff; Rankin, Kenneth S.; Jeys, Lee; Tirabosco, Roberto; Stevenson, Jonathan; et al.
Abstract : Chondrosarcoma (CS) is a rare tumour type and the most common primary malignant bone cancer in adults. The prognosis, currently based on tumour grade, imaging and anatomical location, is not reliable, and more objective biomarkers are required. We aimed to determine whether the level of circulating tumour DNA (ctDNA) in the blood of CS patients could be used to predict outcome. In this multi‐institutional study, we recruited 145 patients with cartilaginous tumours, of which 41 were excluded. ctDNA levels were assessed in 83 of the remaining 104 patients, whose tumours harboured a hotspot mutation in IDH1 / 2 or GNAS . ctDNA was detected pre‐operatively in 31/83 (37%) and in 12/31 (39%) patients postoperatively. We found that detection of ctDNA was more accurate than pathology for identification of high‐grade tumours and was associated with a poor prognosis; ctDNA was never associated with CS grade 1/atypical cartilaginous tumours (ACT) in the long bones, in neoplasms sited in the small bones of the hands and feet or in tumours measuring less than 80 mm. Although the results are promising, they are based on a small number of patients, and therefore, introduction of this blood test into clinical practice as a complementary assay to current standard‐of‐care protocols would allow the assay to be assessed more stringently and developed for a more personalised approach for the treatment of patients with CS. Abstract : In this multi‐institutional study, we detected the amount of circulating tumour DNA (ctDNA) in the blood of patients with chondrosarcoma. We recruited 145 patients, and ctDNA levels were assessed in patients with tumours carrying IDH1 / 2 or GNAS mutations. We found that ctDNA levels offered a more accurate identification of high‐grade tumours than pathology and were additionally associated with poor prognosis.